La transition énergétique américaine : l’impossible décroissance - Bruno Bourliaguet (Développement Durable et Territoires)
The Obama administration wants to decarbonize electricity production by “a bridge” using unconventional sources such as shale gas. Although this presidency is aware of the climate issue, this approach which never limits the economic growth remains politically pragmatic. We show in this article how this policy is part of the agenda of Obama’s technocrats and the consequences of this alliance on the expression of dissenting scientific opinions.